THAHARAH TERINTEGRASI KESEHATAN PRESPEKTIF MIKROBIOLOGI BAGI PRA LANSIA - Ikfi Khoulita; Muhammad Iqbal Filayani; Fitriyah; Anisa Tri Banu Wati (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
Integrated microbiological health taharahwas held to respond to participants' low compliance withfiqh purification requirements and their lack of understanding of the basics ofmicrobiological health. Through an approach that combines religious and scientific perspectives, this training aims to provide a comprehensive understanding of theimportance of ritual hygiene and its impact on health. Researchers used a qualitative descriptive approachwith an evaluative study design to analyze the effectiveness ofmicrobiological health-integrated thaharah training. The resultsof the activity showed an increase in participants' awareness in correctly applying the rules ofthaharah fiqh, accompanied by a new understanding of the role ofmicroorganisms and the health risks of improper hygiene practices. The integration of fiqh and microbiology emphasizes that thaharah is not only areligious obligation, but also a disease prevention mechanism that is in line withmodern health principles. Thus, this training contributessignificantly to strengthening participants' religious and health literacy, as well asserving as a relevant educational model for efforts to improve clean,healthy, and sharia-compliant behavior in the context of today's Muslim society.